2020
DOI: 10.1002/brb3.1571
|View full text |Cite
|
Sign up to set email alerts
|

Subjective feeling of re‐experiencing past events using immersive virtual reality prevents a loss of episodic memory

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…2c,d). Previous work has revealed that modulations of BSC not only alter body- and self-related processes 24-26 , but also affect spatial representation and episodic memory 27,29,65-67 . Second, we extended previous BSC research to the field of spatial navigation and grid cells and successfully modulated BSC by enhancing self-identification with the avatar during spatial navigation 40-43,68,69 .…”
Section: Discussionmentioning
confidence: 99%
“…2c,d). Previous work has revealed that modulations of BSC not only alter body- and self-related processes 24-26 , but also affect spatial representation and episodic memory 27,29,65-67 . Second, we extended previous BSC research to the field of spatial navigation and grid cells and successfully modulated BSC by enhancing self-identification with the avatar during spatial navigation 40-43,68,69 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that coherent perceptions of bodily self in space are critical for optimal memory performance, implying that we are better able to remember information if it is encountered when we have a consistent sense of our bodies to ground our experiences ( Bergouignan et al., 2014 ; Bréchet et al., 2019 , 2020 ; Tacikowski et al., 2020 ). However, these studies have either not investigated how the fundamental perception of one's body as belonging to oneself influences memory for lifelike events, and/or failed to provide clear measures of memory accuracy and key subjective properties of memory retrieval (i.e., reliving, emotional intensity, and belief in memory accuracy).…”
Section: Introductionmentioning
confidence: 99%
“…The multisensory body representation that underpins the core bodily self is produced through the continuous integration of information from multimodal sensory inputs at the level of cortical multisensory association areas (Blanke et al, 2015;Guterstam, Björnsdotter, Bergouignan, et al, 2015;Preston & Ehrsson, 2016). This represents a major advantage over virtual reality experiments conducted using avatars, where the sense of bodily self and its location in space is not explicitly controlled and manipulated, and illusory out-body experiences are not elicited as in the current study (Bréchet et al, 2020;Iriye & St. Jacques, 2020;Mooren et al, 2016). Our experimental manipulation consisted of spatially and temporally correlated visual, auditory, and somatosensory signals (Bergouignan et al, 2014;Bergstrom et al, 2017;Ehrsson, 2007;Guterstam & Ehrsson, 2012), which caused changes in the central perceptual construct of the participant's own body in space.…”
Section: Discussionmentioning
confidence: 97%